Wind tunnel test and numerical simulation of wind characteristics at a bridge site in mountainous terrain. Issue 8 (August 2017) - Li, Yongle; Xu, Xinyu; Zhang, Mingjin; Xu, Youlin
Wind tunnel test and computational fluid dynamics simulation were conducted to study the wind characteristics at a bridge site in mountainous terrain. The upstream terrains were classified into three types: open terrain, open terrain with a steep slope close to the bridge, and open terrain with a ridge close to the bridge. Results obtained from the two methods were compared, including mean speed profiles in the vertical direction and variations of wind speed and angle of attack along the bridge deck. In addition, turbulence intensities at the bridge site obtained from wind tunnel test were discussed. For mean speed profiles in the vertical direction, two methods are reasonably close for open terrain, while mountain shielding effects are evident for open terrain with a steep slope for both the methods, but the extents of effects appear different. Wind speed and angle of attack along the bridge deck are mainly influenced by the local terrain. Strong downslope wind is generated at the lee slope for the case of wind normal to top of the ridge. The comparative results are expected to provide useful references for the study of wind characteristics in mountainous terrain in the future.